A Comparative Study on The Electrochemical Properties of Hydrothermal and Solid-State Methods in The NCM Synthesis for Lithium Ion Battery Application - Sylvia Ayu Pradanawati; Eduardus Budi Nursanto; Afif Thufail; Ahmad Zaky Raihan; Sugianto Sugianto; Haryo Satriya Oktaviano; Hanida Nilasary; Achmad Subhan; Agung Nugroho (Department of Chemical Engineering, Universitas Gadjah Mada, 2022)
In this article, we report and compare the synthesis method of the active cathode materials based on nickel‐cobalt‐manganese (NCM) for lithium-ion battery application. We evaluate the hydrothermal and solid-state reaction method in NCM-622 synthesis, the material characterizations, and the battery performance. Based on the analytical results using X-ray diffraction (XRD), particles synthesized using hydrothermal and solid-state methods exhibit a highly crystalline NCM phase. NCM particles synthesized using solid-state reaction exhibit high-rate performance up to 10 C. The electrochemical impedance spectroscopy analysis shows that the charge transfer resistance (Rct) of NCM synthesized by the solid-state reaction (SSR) method was 25.9% lower than hydrothermal. Meanwhile, the ionic diffusivity of the SSR sample was 38.5% higher than the hydrothermal sample. These two factors lead to better performance when tested in a lithium-ion battery.